Early Childhood ESL Learning in Dhaka and Kolkata: Analyzing Public Primary Schools’ Learning Environments and Learning Strategies of Pupils - Probal Roy Chowdhury (Journal of Education and Learning Research, 2025)
This article aims to present the findings of an international comparative research conducted in the cities of Dhaka (Bangladesh) and Kolkata (India), in the field of early childhood ESL learning. It specifically focuses on language learning environments and ESL learning strategies used by the pupils of public primary schools. Both the cities are situated in the eastern part of the Indian subcontinent and belonged to the same province and country before the partition of India in 1947, sharing Bengali as a common first language. Many public primary schools in both the cities offer English only as a second language to pupils. School-attending early childhood learners are addressed as pupils interchangeably throughout the article. Using qualitative methodology, it is found that infrastructural problems and absence of advanced ESL teaching techniques in public primary classrooms persist in both the cities. Distrust between guardians and teachers adversely affects pupils’ ESL learning in both the cities. Learning environments of both the cities fail to motivate early childhood ESL learners. Over-dependence on memory-related strategies to learn ESL among the pupils is also observed. Learning L1 (Bengali) and L2 (English) at the same time, especially in a classroom setting, creates problems for some pupils. It is discovered comparatively that in a formal learning environment all skills related to and aspects of early childhood ESL learning are not paid equal amount of attention.